Torsional effect of the single-bay masonry building considering seismic wave incident angle. (October 2022) - Liang, Wei; Xia, Lei; Zhu, Zhanyuan; Mou, Sijia; Zou, Zuyin; Yuan, Shucheng
Abstract: Single-bay masonry building is the main structure form of rural houses in Southwest China. In the investigation of earthquake damage in Lushan earthquake, it is found that this type of structure has serious torsional damage. In this paper, the torsional effect was verified with 1/6 scale model while the torsional responses of some actual size models were simulated by self-compiled program. Under the coupling action of translation and torsion, the effects of seismic wave incident angle and structural geometric dimension on the torsional response of structure were analyzed. The results showed that the incident angle of seismic wave and the structural irregularity were the important reasons which caused the torsional failure of the structure. When the incident angle of the seismic wave was about 60°, the torsional response of the structure was the strongest. Besides, in order to reduce the influence of torsional effect, the eccentricity ratio should be smaller than 6%, and the number of storey should better be three or less.